2021
DOI: 10.1158/1078-0432.ccr-21-0474
|View full text |Cite
|
Sign up to set email alerts
|

Pyrotinib Treatment in Patients With HER2-positive Metastatic Breast Cancer and Brain Metastasis: Exploratory Final Analysis of Real-World, Multicenter Data

Abstract: Purpose: Patients with HER2-positive (HER2+) metastatic breast cancer (MBC) have poor prognoses. Pyrotinib has shown promising antitumor activity in MBC patients to improve progression-free survival (PFS). However, findings based on real-world data to analyze whether pyrotinib affects overall survival (OS) remain scarce. Experimental design:This real-world study is an exploratory analysis of brain metastasis (BM) and the final update of our preceding study of 168 patients with HER2+ MBC. PFS, OS, tumor mutatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 42 publications
4
30
2
Order By: Relevance
“…Our study is among the few studies to obtain OS data for BM, and the 18.0 months of mOS in our study was also better than the 13.93 months of mOS in another clinical study conducted by Anwar et al. [ 25 ]. The sample size of Anwar, M.’s study was relatively small (39 cases), and only 5 cases (12.8%) were given pyrotinib plus nab-paclitaxel regimen in comparison to 17 cases (27.9%) in our study.…”
Section: Discussionsupporting
confidence: 41%
“…Our study is among the few studies to obtain OS data for BM, and the 18.0 months of mOS in our study was also better than the 13.93 months of mOS in another clinical study conducted by Anwar et al. [ 25 ]. The sample size of Anwar, M.’s study was relatively small (39 cases), and only 5 cases (12.8%) were given pyrotinib plus nab-paclitaxel regimen in comparison to 17 cases (27.9%) in our study.…”
Section: Discussionsupporting
confidence: 41%
“…The initial benefit of pyrotinib in combination with chemotherapy was not statistically significant compared with pyrotinib alone, probably because our group of patients, with a relatively short follow‐up period, had not all yet reached the end of the event. In another just published study, 25 the median PFS and OS were 8.67 and 13.93 months, respectively in the 39 HER2‐positive breast cancer patients with brain metastases, and they also confirmed the prolonged survival of combined therapy of pyrotinib with surgery or radiation in these patients.…”
Section: Discussionmentioning
confidence: 52%
“…It would provide important references for our clinical decision-making. (2) In recent years, relevant studies have reported that small-molecule tyrosine kinase inhibitors could improve the progression and prognosis of BM in HER2-positive BC patients (33)(34)(35). We expect that there could be some clinical trials about pre-emptive medical interventions in the future.…”
Section: Discussionmentioning
confidence: 99%